A DECISION-ANALYTIC, SIMULATION BASED MANAGEMENT MODEL FOR A TWO-SHIFTS QUEUE SYSTEM WITH CUSTOMER RENEGING - Chew Hernández, Mario Luis; Viveros Rosas, Leopoldo; Velázquez Romero, Verónica (JEMIS (Journal of Engineering & Management in Industrial System), 2023)
This paper shows a management model for a queuing system operating two shifts and where client reneging is present. The model provides the optimal active server policy considering lost clients and cost. Using influence diagrams and decision trees, the proposed model implements a Bayesian scheme to update the initial knowledge in response to the observed number of lost customers in the first shift. In addition, a utility function is used to represent the preferences of the decision-maker and simulation to determine the consequences and probabilities of the trees. The results are displayed as the number of active servers recommended for each shift, according to the preferences of the decision-maker and the clients lost in the first shift. For the case study, it is found that if the weight for the number of lost clients in the utility function (kNL) is less than 0.63, a single server should be used in both shifts, while when kNL is greater than said value, the first shift opens one server, while a second one is activated for the next shift depending on the number of lost clients in the first shift.